2020
DOI: 10.3390/ijerph17176349
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity Trajectories among Persons of Turkish Descent Living in Germany—A Cohort Study

Abstract: Physical activity (PA) behavior is increasingly described as trajectories taking changes over a longer period into account. Little is known, however, about predictors of those trajectories among migrant populations. Therefore, the aim of the present cohort study was to describe changes of PA over six years and to explore migration-related and other predictors for different PA trajectories in adults of Turkish descent living in Berlin. At baseline (2011/2012) and after six years, sociodemographics, health behav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 51 publications
0
2
1
Order By: Relevance
“…Among the studies that reported associated factors with SB increase, factors were changes in working situation (working from home or having lost a job) [ 46 ], male sex, and non-smoking [ 47 ]. While the previous results of this cohort study showed that German citizenship and German as preferred questionnaire language were associated with a positive PA trajectory [ 23 ], in the present study none of the migration-related variables was associated with decreased PA or increased SB. Since the results of this study were comparable with other studies conducted in Germany, at least for Berlin there does not seem to be a large difference between the population of origin and persons with a Turkish background.…”
Section: Discussioncontrasting
confidence: 86%
See 1 more Smart Citation
“…Among the studies that reported associated factors with SB increase, factors were changes in working situation (working from home or having lost a job) [ 46 ], male sex, and non-smoking [ 47 ]. While the previous results of this cohort study showed that German citizenship and German as preferred questionnaire language were associated with a positive PA trajectory [ 23 ], in the present study none of the migration-related variables was associated with decreased PA or increased SB. Since the results of this study were comparable with other studies conducted in Germany, at least for Berlin there does not seem to be a large difference between the population of origin and persons with a Turkish background.…”
Section: Discussioncontrasting
confidence: 86%
“…There is a study from Australia that investigated coping strategies among migrants during the pandemic, but without taking physical activity into account [ 22 ]. A recent study investigating a Turkish migrant sample showed that PA and SB changes depended, among other things, on migration-related factors like citizenship, and the preferred language when completing a questionnaire; however, these results were reported before the COVID-19 pandemic [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Being registered in a refugee camp or reception centre served to define migrant status in 11 articles, while citizenship (outside Germany) was used in 4 articles. In three articles, name-based algorithms were applied to register data for the identification of persons with migration background 22–24…”
Section: Resultsmentioning
confidence: 99%